2013
DOI: 10.1161/circresaha.112.270223
|View full text |Cite
|
Sign up to set email alerts
|

Tbx1 Genetically Interacts With the Transforming Growth Factor-β/Bone Morphogenetic Protein Inhibitor Smad7 During Great Vessel Remodeling

Abstract: Rationale: Growth and remodeling of the pharyngeal arch arteries are vital for the development of a mature great vessel system. Dysmorphogenesis of the fourth arch arteries can result in interruption of the aortic arch type B, typically found in DiGeorge syndrome. Tbx1 haploinsufficient embryos, which model DiGeorge syndrome, display fourth arch artery defects during formation of the vessels. Recovery from such defects is a documented yet unex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 48 publications
6
41
0
Order By: Relevance
“…4–5) and the online Figure IIB in (Papangeli and Scambler, 2013). Consistent with these data, we found that integrin α5 was efficiently depleted from arch artery endothelium in integrin α5 flox/− ; Mesp1 Cre+ mutants (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4–5) and the online Figure IIB in (Papangeli and Scambler, 2013). Consistent with these data, we found that integrin α5 was efficiently depleted from arch artery endothelium in integrin α5 flox/− ; Mesp1 Cre+ mutants (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Four RLIM-affected males presented with CHD resembling CHD types described in the 22q11-deletion syndrome. TBX1, which resides in this 22q11 chromosomal region, is very dose sensitive and is involved in the formation of the secondary heart field together with its targets, e.g., SMAD7 [79], SHH, FGF8 and BMP4 [80], indicating once again the involvement of subtle (dose) dysregulation of RLIM downstream effectors can have consequences for the expression of the clinical phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…To identify putative shared targets, we followed a candidate gene approach. We considered three Tbx1 target genes that are known to interact with Tbx1 during fourth PAA development: Gbx2, Smad7, and Wnt5a (17,24,25). We first tested the expression of these genes in WT, Tbx1 +/− , Trp53 +/− , and Tbx1 +/− ; Trp53 +/− E8.5 embryos using quantitative reverse transcription PCR.…”
Section: Trp53 Mutation Modifies the Hypomorphic But Not The Null Tbx1mentioning
confidence: 99%